2018
DOI: 10.1080/14756366.2018.1493473
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis, in vitro antiproliferative activity and apoptosis-inducing studies of 1-(3′,4′,5′-trimethoxyphenyl)-3-(2′-alkoxycarbonylindolyl)-2-propen-1-one derivatives obtained by a molecular hybridisation approach

Abstract: Inhibition of microtubule function using tubulin targeting agents has received growing attention in the last several decades. The indole scaffold has been recognized as an important scaffold in the design of novel compounds acting as antimitotic agents. Indole-based chalcones, in which one of the aryl rings was replaced by an indole, have been explored in the last few years for their anticancer potential in different cancer cell lines. Eighteen novel (3′,4′,5′-trimethoxyphenyl)-indolyl-propenone derivatives wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Microtubules are intracellular polymers involved in the regulation of a large number of cellular processes, including proliferation, division, determination and maintenance of cellular shape, motility, and intracellular transport. 1 They are highly dynamic structures composed of multiple heterodimers of α- and β-tubulin, and they undergo alternating polymerization and depolymerization phases. 2 Disrupting this dynamic equilibrium interferes with cell division and leads to cell death.…”
Section: Introductionmentioning
confidence: 99%
“…Microtubules are intracellular polymers involved in the regulation of a large number of cellular processes, including proliferation, division, determination and maintenance of cellular shape, motility, and intracellular transport. 1 They are highly dynamic structures composed of multiple heterodimers of α- and β-tubulin, and they undergo alternating polymerization and depolymerization phases. 2 Disrupting this dynamic equilibrium interferes with cell division and leads to cell death.…”
Section: Introductionmentioning
confidence: 99%
“…A search for molecules that present the aromatic ring motif in their structure with their cytotoxic activity in the HeLa cell line, reported through the IC 50 obtained by the MTT colorimetric assay, [49][50][51][52][53][54][55][56][57][58][59][60][61] was carried out. From this search a total of 170 molecules were identified that met our proposed criteria.…”
Section: Search For Molecules and Molecular Designmentioning
confidence: 99%
“…A class of novel chalcone derivatives containing 3′,4′,5′- trimethylyl and indole fragments 29 ( Figure 20 ) have been obtained, and their antiproliferative activity against a panel of HeLa, human colon carcinoma (HT29), MCF-7, and human lymphoma (HL-60) cells (3–5 × 10 4 cells) lines also tested 68 . The majority of the synthesised compounds showed superior activities to the reference drug.…”
Section: Aromatic Ring Modificationsmentioning
confidence: 99%